2016
DOI: 10.1186/s12966-016-0336-3
|View full text |Cite
|
Sign up to set email alerts
|

Promoting and maintaining physical activity in the transition to retirement: a systematic review of interventions for adults around retirement age

Abstract: It has been argued that transition points in life, such as the approach towards, and early years of retirement present key opportunities for interventions to improve the health of the population. Research has also highlighted inequalities in health status in the retired population and in response to interventions which should be addressed. We aimed to conduct a systematic review to synthesise international evidence on the types and effectiveness of interventions to increase physical activity among people aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 76 publications
(44 reference statements)
0
68
0
Order By: Relevance
“…While moving into retirement is considered a significant transition in life, very few physical activity intervention studies have focused on this critical period in life [22]. Our results suggests that two potential time periods could be particularly suitable for interventions.…”
Section: Discussionmentioning
confidence: 87%
“…While moving into retirement is considered a significant transition in life, very few physical activity intervention studies have focused on this critical period in life [22]. Our results suggests that two potential time periods could be particularly suitable for interventions.…”
Section: Discussionmentioning
confidence: 87%
“…Seven reviews mentioned ethnicity [30,31,32,33,34,44,46] and reported that participants were primarily white with a small proportion of ethnic minorities. The majority of reviews either specifically focused on participants with no pre-existing medical condition or did not specify any medical conditions, with the exception of three reviews [32,33,43], which also included patient populations (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The most common theoretical framework was Social Cognitive Theory (SCT), mentioned in nine reviews [30,32,33,36,39,41,42,43,44] and reported to have been used in at least 44 studies. The Transtheoretical Model (TTM) was the second most common framework, featuring in six reviews [32,33,41,42,44,43] and at least 21 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our observation of sports participation increasing after retirement indicates that retirement seems to be one of the life events where individuals might be especially receptive to PA promoting interventions [ 13 ]. Surprisingly, very few interventions target this time [ 52 ].…”
Section: Discussionmentioning
confidence: 99%